Pre-service Physics Teachers’ Perceptions of STEM-EDP Learning in Addressing Water Turbidity Issues - Atin Nuryadin; Lambang Subagiyo; Nurul Fitriyah Sulaeman; Muliati Syam (AL-ISHLAH: Jurnal Pendidikan, 2026)
Water turbidity, often resulting from mining and agricultural activities, poses significant risks to ecosystems and human health. Addressing this issue requires innovative, interdisciplinary approaches. This study explores how the integration of STEM with the Engineering Design Process (STEM-EDP) supports pre-service physics teachers in designing solutions to water turbidity problems.A qualitative descriptive design was employed involving 39 pre-service physics teachers from two classes, organized into seven groups. Participants engaged in a four-session project using STEM-EDP worksheets to design and construct water turbidity meters and filtration devices from accessible materials. Data were collected through open-ended questions capturing students’ learning experiences and analyzed thematically.The findings indicate that participants developed critical and creative thinking, as well as collaboration and communication skills. They demonstrated a deeper understanding of STEM integration by applying concepts such as light scattering and filtration, utilizing smartphone lux meters, and performing calculations related to water discharge and cost efficiency. The STEM-EDP approach enabled students to connect scientific and engineering principles with real-world environmental problems.The study concludes that STEM-EDP is an effective pedagogical approach for enhancing pre-service teachers’ problem-solving abilities and interdisciplinary understanding. Incorporating hands-on, context-based STEM-EDP activities in teacher education programs can better prepare future educators to design meaningful, real-world learning experiences.